2019
DOI: 10.36351/pjo.v35i1.862
|View full text |Cite
|
Sign up to set email alerts
|

Central Macular Thickness: a Comparative Study of Diabetics Vs Healthy

Abstract: Purpose: To compare the central macular thickness amongst diabetics with that of healthy population by using Optical Coherence Tomography. Study Design: Case control study. Place and Duration of Study: Department of Ophthalmology Unit I, Civil Hospital Karachi from 5th March 2012 to 4th September 2012. Material and Methods: We randomly selected patients with diabetes (cases) and healthy patients (control) with clinically normal macula and no diabetic retinopathy. Detailed relevant his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…This finding was consistent with Eriksson and Alm et al 23 who observed a negative connection between retinal thickness and age groups. On contrary, Khan et al 1 suggested that in his study, a significant correlation emerged on comparing the CMT values and, age in healthy subjects. Similarly, the author also had insignificant findings when comparing the CMT values and age with diabetic subjects.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This finding was consistent with Eriksson and Alm et al 23 who observed a negative connection between retinal thickness and age groups. On contrary, Khan et al 1 suggested that in his study, a significant correlation emerged on comparing the CMT values and, age in healthy subjects. Similarly, the author also had insignificant findings when comparing the CMT values and age with diabetic subjects.…”
Section: Discussionmentioning
confidence: 68%
“…Diabetes is the most prevalent metabolic disorder with a risk factor of causing multiple organ damage affecting humans worldwide. 1 Combination of diabetic retinopathy and diabetic maculopathy may cause serious sight threatening disturbances, leading to blindness. 2 It is necessary to understand the concept of macular thickness in normal individuals because of the occurrence of multiple systemic and ocular diseases.…”
Section: Introductionmentioning
confidence: 99%